Inhibition of mammalian cathepsins by Plesiomonas shigelloides - Pavlova, A; Krovácek, K; Ciznár, I; Gonzalez-Rey, C (Folia microbiologica, 2006)
To study molecular mechanisms underlying self-defense of the bacterial pathogen Plesiomonas shigelloides against host inflammatory and immune responses, we evaluated its interactions with mammalian papain-like cathepsins that are essential for host immunity. When grown under anaerobic, but not aerobic, conditions, P. shigelloides was shown to bind and inhibit papain, a model representative of the papain family of cysteine proteinases. This points to mammalian cathepsins as likely physiological targets of a novel cysteine-proteinase inhibitor expressed on bacterial cell surface. Both papain and mammalian cathepsins L and B were inhibited by periplasmic extracts of aerobically and anaerobically grown bacteria, the inhibitory activity being higher in the latter. Inhibition by both intact cells and periplasmic samples was rapid and efficient. The results suggest a possible defensive role of bacterial inhibitors of cathepsins during invasion of a mammalian host. The bacteria thus may modulate host protective responses through inhibiting cathepsins involved in antigen processing and presentation.
Keywords: Animals; Mammals; Cathepsin L; antigeny bakteriální; Periplasm; prezentace antigenu; lidé; Cathepsins; periplazma; kathepsin B; papain; Cysteine Proteinase Inhibitors; cysteinové endopeptidasy; savci; Cysteine Endopeptidases; kathepsin L; kathepsiny; Antigens, Bacterial; Papain; zvířata; Cathepsin B; inhibitory cysteinových proteinas; Antigen Presentation; Plesiomonas; Humans